The Influence of Gadget on Wards Social Interaction of Adolescents at SMK Gunung Sari 1 Makassar - Musaidah Musaidah (State Islamic University of Sunan Ampel, 2019)
Social interaction denotes adaptation with surroundings between individual and individual, individuals and groups, and groups and groups. The purpose of this research is to know the influence of gadget towards the social interaction of juveniles at SMK Gunung Sari 1 Makassar. The type of this research is quantitative descriptive using Simple Random Sampling with the number of 41 samples which means that the analysis of scientific method used number starting from data collection, data interpretation and its result. The purpose of this is to know the influence of independent variable, gadget (the intensity of use, communication and online game wich correlation wards dependent variable (social interaction of teenagers). Based on the statistical test by using Correlation test in this analysis used is the correlation with ameaningÎ±= 0.05 an confidence interval, the intensity of gadget use was obtained by the value of p = 0.000 with the value of r = 0.615 which means that the result of the hypothesis mentioned that there was an effect of the intensity of the gadget use towards the social interaction of adolescents with moderate relationship and positive direction (unidirectional). The variable gadget as the means of communication to the variable of online game addiction obtained a value of p=0.000 with r=0.689. Thus, there is an influence of online game towards the social interaction of juveniles with strong relationships and unidirectional.